Responsabilidade civil das concessionárias de rodovias: lesão individual por dano ambiental em face de acidente na via, decorrente de deficiências de construção, conservação, manutenção ou sinalização de rodovias - Osorio, Jussara Maria Manassi (My University, 2014)
This study deals with the civil responsibility of highway concession holders and individual harm stemming from environmental damage caused by road accidents, resultant from improper construction, maintenance or signposting of highways. It deals with aspects of civil responsibility and the concession of highways with toll systems. It is a brief study of concession granting, giving rise to the complex of relationships established between the State, the private concession holder, users and third parties, analyzing the concession contract, its characteristics, and the obligations of the parties. This study spans civil responsibility and the responsibility of the State, focusing on objective responsibility and norm § 6° of art. 37 of the Federal Constitution. Special attention is given to environmental damage, its characteristics, civil responsibility and the responsibility of the State for environmental damage, objective responsibility and the theories that inform them, focusing on individual harm caused by environmental damage and its reparation examining the provisions in Brazilian law. It deals with the responsibility of the highway concession holders focused on application of art. 37, § 6° of the Fede ral Constitution, which extended the responsibility of the State to highway concession holders. It examines the law that has resulted in the civil responsibility of concession holders for damages caused by accidents resulting from improper construction, maintenance or signposting of highways and that relative to civil responsibility for individual harm caused by environmental damage.
O trabalho aborda a responsabilidade civil das concessionárias de rodovias e a lesão individual devido a dano ambiental em face de acidente na via, decorrente de deficiências de construção, conservação, manutenção ou sinalização das rodovias. Expõe aspectos da responsabilidade civil e a concessão de rodovias com pedágio, em breve estudo do instituto da concessão, que dá origem ao complexo de relações que se estabelecem entre o Estado, a concessionária privada, o usuário e terceiro, analisando o contrato de concessão, suas características, as obrigações das partes. Abrange o estudo da responsabilidade civil e da responsabilidade civil do Estado, com enfoque na responsabilidade objetiva e a norma do § 6° do art. 37 da Constituição Federal. Destaca o dano ambiental, suas características, a responsabilidade civil e a responsabilidade do Estado por dano ambiental, a responsabilidade objetiva e as teorias que a informam, com enfoque na lesão individual decorrente de dano ambiental e sua reparação examinando o previsto no ordenamento jurídico brasileiro. Aborda a responsabilidade das concessionárias de rodovias com enfoque na aplicação do art. 37, § 6°, da Constituição Federal, que estendeu a responsabilidade do Estado às concessionárias de rodovias. Examina jurisprudências que resultaram na responsabilidade civil da concessionária por danos decorrentes de acidentes devido a deficiências de construção, conservação, manutenção ou sinalização de rodovia e relativas à responsabilidade civil por lesão individual decorrente de dano ambiental.
Keywords: Direito; Responsabilidade civil; Lesão individual; Dano ambiental; Responsabilidade do Estado; Concessionárias de rodovias; Acidentes; Deficiências de construção; Conservação; Manutenção; Sinalização; Civil responsability; Individual injury; Environmental damage; Responsibility of the State; Highway concession holders; Accidents; Improper construction; Maintenance; Signposting